2022
DOI: 10.3390/healthcare10030481
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Non-Pharmacological, Non-Surgical Secondary Prevention Strategies in Ischaemic Stroke and TIA in National Stroke Guidelines and Clinical Audit Documents

Abstract: The Stroke Action Plan for Europe (2018–2030) calls for national-level secondary prevention plans that address lifestyle, in addition to prevention medications and surgical interventions. This scoping review examines national stroke care guideline and audit documents across WHO regions to identify non-pharmacological, non-surgical stroke secondary prevention recommendations and associated performance indicators. Using a snowballing methodology, 27 guideline documents met the inclusion criteria. Sixteen (59%) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…It has also been acknowledged as a risk factor for secondary strokes in a Delphi study conducted by a group of international experts in secondary stroke prevention [ 13 ]. A recent scoping review of the national stroke guidelines of 27 countries concluded that psychosocial stress is poorly addressed as a modifiable population attributable risk factor in secondary stroke prevention [ 14 ]. As noted previously, PWA and, indeed, stroke patients with aphasia report high levels of anxiety and psychosocial stress.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been acknowledged as a risk factor for secondary strokes in a Delphi study conducted by a group of international experts in secondary stroke prevention [ 13 ]. A recent scoping review of the national stroke guidelines of 27 countries concluded that psychosocial stress is poorly addressed as a modifiable population attributable risk factor in secondary stroke prevention [ 14 ]. As noted previously, PWA and, indeed, stroke patients with aphasia report high levels of anxiety and psychosocial stress.…”
Section: Introductionmentioning
confidence: 99%
“…For the modified intervention, that will be someone belonging to the stroke community, demonstrating techniques that have been specifically designed for them. This will act as a visual cue that the techniques can be completed by other stroke survivors, demonstrating that the current intervention has been specifically tailored to stroke survivors, which should increase uptake and engagement [31] as well possibly reducing the risk of secondary stroke [9].…”
Section: Discussionmentioning
confidence: 99%
“…By having an intervention that is specifically tailored to reduce post-stroke stress and anxiety, it is more likely that stroke survivors and caregivers will engage with the materials and achieve the desired frequency of practice, which will lead to enhanced intervention effectiveness. This could also reduce the risk of a secondary stroke [9]. Informed Consent Statement: Informed consent was obtained from all subjects involved in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hall et al (2022), in their scoping review of contemporary stroke guideline documents and clinical audits, shine a spotlight on the current lack of clear direction for clinicians in addressing secondary prevention beyond pharmacological or surgical management [ 2 ]. This work highlights the imperative to raise awareness amongst researchers and clinicians of the urgent need for high-quality holistic secondary prevention stroke care initiatives that will help improve outcomes (medical, psychological, social, and societal) for stroke patients and their families.…”
mentioning
confidence: 99%